2018
DOI: 10.1177/1569186118759611
|View full text |Cite
|
Sign up to set email alerts
|

Use of parametric speaker for older people with dementia in a residential care setting: A preliminary study of two cases

Abstract: Objective/BackgroundOlder people with dementia often show behavioural and psychological symptoms of dementia such as agitation, aggression, and depression that affect their activities of daily living, and hence reduce the quality of life of their caregivers. The aim of this study was to investigate the effects of a new technological intervention—a parametric speaker, creating a narrow personal acoustic environment, which may reduce the manifestation of behavioural and psychological symptoms of dementia symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Residents in care facilities might be stimulated even more through technologies and "active" tools that are more person-centered. An example is the use of a parametric speaker, a high-directional loudspeaker transmitting sound in a narrow acoustic space, to create personal space in a common room (Nishiura et al, 2018). Actively designing soundscapes, for instance, using the residents' sensitivity and preference, might be another valuable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Residents in care facilities might be stimulated even more through technologies and "active" tools that are more person-centered. An example is the use of a parametric speaker, a high-directional loudspeaker transmitting sound in a narrow acoustic space, to create personal space in a common room (Nishiura et al, 2018). Actively designing soundscapes, for instance, using the residents' sensitivity and preference, might be another valuable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of external stimuli is a prominent cause of negative emotions in older people with dementia. Studies have found that sensory stimulation through acoustic intervention can reduce the agitation behavior of older people with dementia (Riley-Doucet and Dunn, 2013 ; Nishiura et al, 2018 ; Syed et al, 2020 ). Therefore, how to create a healthy acoustic environment for the older with dementia has become an urgent problem for countries worldwide to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Not all residents found the Virtual Reality Forest experience to be positive Neal et al [ 15 ] 2020 The use of technology to promote meaningful engagement for adults with dementia in residential aged care: A scoping review Australia Scoping review Twenty (20) studies with 4 to 415 participants. Three (3) studies not reporting the sample size Different social robots explored for their potential benefit to facilitate residents’ leisure activities Robotics Engagement Engagement not consistent across studies Technologies were reported as providing enjoyable experience, improving well-being and preventing negative outcomes such as agitation or distress Nishiura et al [ 38 ] 2018 Use of a parametric speaker for older people with dementia in a residential care setting: A preliminary study of two (2) cases Japan Quantitative, Multiple case study Two (2) residents. A 78-year-old man and 90-year-old female A parametric speaker received input from a personal computer to play participant’s favorite pieces of music Multimedia Computer systems Behavioral and psychological symptoms of dementia; Cognitive Function The intervention has significantly decreased residents’ behavioral and psychological symptoms of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…While others reported inconclusive results regarding it [ 27 , 30 , 35 ]. Few other studies examined also cognitive function outcome [ 18 , 38 , 44 , 45 , 52 , 53 ]. Interventions using multimedia computer systems and virtual reality were particularly noted for their potential to improve cognitive functioning among seniors with NCD in LTC [ 44 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation